Novel Coronavirus Outbreak and Career Development: A Narrative Approach Into the Meaning for Italian University Graduates - Parola, Anna (Frontiers in Psychology, 2020)
Introduction In times of economic crisis, the literature shows that young people have always been in the high-risk category. The COVID-19 outbreak and the consequence on the economic level have increased the sense of uncertainty and precariousness experienced by young people. The current scenario has forced young people at the school-to-work transition point to re-think their career plans. Although the difficulties of the school-to-work transition already lead to distress and mental health problems in young people, the slowdown imposed by the coronavirus could add up to these difficulties. The present study aimed to explore the process of career development and career planning in the coronavirus era. Twenty Italian university graduates were involved. Methods A quantitative measure was used to evaluate the affective (positive/negative) experience. A narrative prompt was used to understand the individual dimensions of career planning. Cluster analysis was carried out by an unsupervised ascendant hierarchical method to explore the themes of the narration. Results Italian young adults have tended to experience negative affects in the recent weeks of quarantine. The themes highlighted in the narratives showed that Italian young adults experience feelings of fear, uncertainty, and anxiety about the post-pandemic future. Conclusion The results appear as a starting point to re-think possible interventions for this group post-lockdown and post-pandemic.